2014
DOI: 10.1051/0004-6361/201424076
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation and chemistry of N2in the circumstellar envelope of carbon-rich AGB stars

Abstract: Context. The envelopes of asymptotic giant branch (AGB) stars are irradiated externally by ultraviolet photons; hence, the chemistry is sensitive to the photodissociation of N 2 and CO, which are major reservoirs of nitrogen and carbon, respectively. The photodissociation of N 2 has recently been quantified by laboratory and theoretical studies. Improvements have also been made for CO photodissociation. Aims. For the first time, we use accurate N 2 and CO photodissociation rates and shielding functions in a mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 68 publications
(107 reference statements)
5
56
0
Order By: Relevance
“…The conclusion was consistent with the previous observations (e.g., Bujarrabal et al 1994) and was further confirmed via the observations of Decin et al (2008). In previous work we developed a model that, for the first time, accurately treated the photodissociation of two significant parent species, CO and N 2 , in the CSE of a C-rich star, IRC +10216 (Li et al 2014). Here, we adapt this model to study the chemistry of O-rich AGB stars.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…The conclusion was consistent with the previous observations (e.g., Bujarrabal et al 1994) and was further confirmed via the observations of Decin et al (2008). In previous work we developed a model that, for the first time, accurately treated the photodissociation of two significant parent species, CO and N 2 , in the CSE of a C-rich star, IRC +10216 (Li et al 2014). Here, we adapt this model to study the chemistry of O-rich AGB stars.…”
Section: Introductionsupporting
confidence: 88%
“…The bestinvestigated AGB star, both observationally and theoretically, is the nearest C-rich star, IRC +10216 (e.g., Millar et al 2000;Cernicharo et al 2000;Woods et al 2003;Cordiner & Millar 2009;Decin et al 2010a;De Beck et al 2012;Cherchneff 2012; East Asian Core Observatories Association (EACOA). McElroy et al 2013;Li et al 2014). To date, more than 44% of the 180 identified species in the interstellar medium (ISM) or CSEs 1 have been detected in this star, with some being first detections in astrophysical environments, e.g., the cyanide anion CN − (Agúndez et al 2010b) and FeCN (Zack et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…In lower-metallicity and/or extragalactic environments, the interstellar UV field may be very different (e.g., McDonald et al 2015). The results on the circumstellar CO chemistry of Mamon et al (1988) are frequently used in CO line radiative transfer modelling, but recent studies suggest that these may have to be revised (Li et al 2014(Li et al , 2016. Descriptions of the implementation of CO line radiative transfer in numerical codes are given in, e.g., Groenewegen (1994a), Schöier and Olofsson (2001), and Decin et al (2006).…”
Section: Molecular Line Emissionmentioning
confidence: 99%
“…Most notably, C3 is underestimated whereas C5 is overestimated. The calculated values from Millar et al (2000), McElroy et al (2013) and Li et al (2014), shown in Figure 5, predict the column densities of C3 and C5 to be almost equal. Our work suggests that C3 is almost 2 orders of magnitude greater than C5 (see Table 5), which indicates a similar trend to that seen in Cherchneff & Glassgold (1993) where the abundance of C3 was ∼10 times greater than C5.…”
Section: Discussionmentioning
confidence: 83%
“…The total empirical column density in IRC +10216 for neutral carbon is 1.1 × 10 16 cm −2 (Keene et al 1993) and for C2 is 7.9 × 10 14 cm −2 (Bakker et al 1997). chain column densities from a state-of-the-art model by Li et al (2014), that improves the N2 and CO photodissociation rates and shield functions of McElroy et al (2013), is also shown. The primary carbon chains growth pathways (Millar et al 2000) are given by…”
Section: Discussionmentioning
confidence: 95%